PENGARUH MODEL STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SATUAN BAKU PANJANG - Sri Mulyani, Anisa; Isrok'atun; Irawati, Riana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low level of students’ mathematical problem-solving abilities, particularly in the topic of standard units of length. The main objective of this study was to analyze the effect of the STAD learning model on the mathematical problem-solving abilities of third-grade elementary school students. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group. The research population consisted of all third-grade students in Paseh District, while the sample included 30 third-grade students from SDN Paseh I as the experimental class and 33 third-grade students from SDN Cileuksa as the control class. Data were collected through mathematical problem-solving ability tests. The findings revealed that the implementation of the STAD model had a positive effect on students’ mathematical problem-solving abilities, as indicated by an average N-Gain score of 0.48 in the experimental class. Meanwhile, conventional learning also produced a positive effect, but with a lower average N-Gain score of 0.20 in the control class. Therefore, it can be concluded that the STAD learning model exerted a more significant effect, as reflected in the higher improvement of mathematical problem-solving abilities in the experimental class compared to conventional learning in the control class.